Birds: Their portrayals and habits in the agrosystem of the Palmira campus of the Alliance of Bioversity International and CIAT - Sedano, Raul; Tohme, Joseph; Gallego, Gerardo (2024)
This book details changes in the bird community within a high-intensity agricultural system in the middle basin of the Cauca River valley, Valle del Cauca, Colombia. Approximately 26% of bird species at the Palmira campus are vagrants, while 35% are aquatic species found in artificial wetlands. Using long-term data and baseline lists, we update local species extinction estimates in the context of colonization and recolonization. We describe the region's climate, irrigation, and agricultural activities, also offering a paleocological context. In collaboration with the Bioversity International-CIAT Alliance and the University of Valle in Cali, Colombia, we incorporated citizen science data that contributed stories for 41 species. This open-access, 142-page digital book, Volume I, includes illustrations, bird sounds, and narratives about their ecology, evolution, and cultural importance. It was launched alongside the 16th Conference of the Parties to the Convention on Biological Diversity.